Polityka spójności w kontekście interesów krajów członkowskich Unii Europejskiej - Gawlikowska-Huekcel, Krystyna (Cohesion Policy in the Context of the EU and its Member States' Problems, 2008)
The current direction of regional policy is guaranteed by the Treaty's provisions. The policy has been evolving, and today's theoretical debate and discussions carried by the EU institutions and among the member states indicate that advocates of its modifications exist, concerning both the objectives and the amount of expenses allocated. The paper is an attempt to answer the question whether a legitimate danger exists that the policy will undergo considerable changes, or whether its current form and extent will remain unchanged. A number of causes persists that can endanger the current option of the regional policy. The first one is a decreasing tendency of the richest member states to finance it. The second one is an inconclusive assessment of its effects, which is especially important considering the EU priority of increasing the competitiveness and innovativeness of the whole Community. The third one is the future accession of lesser development level that fulfill the criteria of regional support, which will cause an increase of expenses for the cohesion policy.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 10, s. 91-104